2013
DOI: 10.1080/19443994.2012.714629
|View full text |Cite
|
Sign up to set email alerts
|

Chronopotentiometric study of ceramic cation-exchange membranes based on zirconium phosphate in contact with nickel sulfate solutions

Abstract: Martí Calatayud, MC.; García Gabaldón, M.; Pérez-Herranz, V.; Sonia; SERGIO MESTRE (2013). Chronopotentiometric study of ceramic cation-exchange membranes based on zirconium phosphate in contact with nickel sulfate solutions. Desalination and Water Treatment. 51(1): 597-605. doi:10.1080/19443994.2012.714629. Chronopotentiometric study of ceramic cation-exchange membranes based on zirconium phosphate in contact with nickel sulfate solutions. Abstract.In this article, the innovative cation-exchange membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Specically, the deposition of zirconium phosphate was reported to occur uniformly in pores of different diameters. 19 Therefore, it seems that in the present case the addition of starch during the formation of the microporous supports is essential in order to create pores of an optimum diameter where the deposition of ion exchanger takes place preferentially. Moreover, from the evolution of the pore size distributions with n, it can be concluded that the ZrO 2 is signicantly deposited over previously inltrated ZrO 2 particles.…”
Section: Chemical and Morphological Characterizationmentioning
confidence: 90%
See 3 more Smart Citations
“…Specically, the deposition of zirconium phosphate was reported to occur uniformly in pores of different diameters. 19 Therefore, it seems that in the present case the addition of starch during the formation of the microporous supports is essential in order to create pores of an optimum diameter where the deposition of ion exchanger takes place preferentially. Moreover, from the evolution of the pore size distributions with n, it can be concluded that the ZrO 2 is signicantly deposited over previously inltrated ZrO 2 particles.…”
Section: Chemical and Morphological Characterizationmentioning
confidence: 90%
“…Previous studies have demonstrated the suitability of these supports to act as separators in electrochemical reactors. 19,20 Moreover, their pore size distribution can be tuned by adding pore formers to the alumina-kaolin mixture. 20,21 Subsequently, particles of hydrated zirconium dioxide, which provide the membranes with anion-exchange properties, were embedded in the voids of the ceramic supports.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations